Past, Present, and Future Contributions of Cognitive Writing Research to Cognitive Psychology. - Berninger, Virginia Wise (Taylor & Francis, 2012)
This volume tells the story of research on the cognitive processes of writing-from the perspectives of the early pioneers, the contemporary contributors, and visions of the future for the field. Writing processes yield important insights into human cognition, and is increasingly becoming a mainstream topic of investigation in cognitive psychology and cognitive neuroscience. Technological advances have made it possible to study cognitive writing processes as writing unfolds in real time. This book provides an introduction to these technologies. The first part of the volume provi.